The Efects of Male Age on Semen Parameters : Analysis of 1364 Men Attending an Andrology Center (2009)
ABSTRACT: Although the effect of maternal age on fertility is well known, it is unclear whether paternal age also affects fertility. The aim of this retrospective study was to establish an association between the age of the individuals from Medellin, Colombia with semen volume, rapid progressive motility (a), total progressive motility (a þ b) and concentration. We evaluated semen volume using a graduated tube, progressive motility using light microscopy (406) and sperm concentration using a Makler Chamber. Semen samples were grouped according to age into three arbitrary groups (to 30 years; between 31 and 39 years; and to 40 years). The semen volume, rapid progressive motility (a) and total progressive motility (a þ b), concentration and total sperm count were found to be inversely related to age (p5 0.05). The reduction in semen parameters of 1364 men attending an andrology center was associated with increasing age of the individuals.